Mechanical baby pig feeder - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Various types of mechanical units designed to replace lactating brood sows are available. The Mini-Mor Corporation, Omaha, Nebraska, lent Kansas State University a unit designed to raise 36 pigs in individual cages. We are not trying to replace the lactating sow but to save baby pigs when they lose their mothers, or when a sow has more pigs than teats. The unit also could be used with large litters, for pigs that are pushed back and obviously are not getting enough to eat when a few days old.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Baby pig feeder